2016
DOI: 10.1002/mats.201670007
|View full text |Cite
|
Sign up to set email alerts
|

Macromol. Theory Simul. 3/2016

Abstract: Front Cover: The glass transition behaviors and mechanical properties of the π‐conjugated polymers, polyacetylene (PA) and poly(para‐phenylene vinylene) (PPV), are predicted using atomistic simulations and compared with experimental measurements. The cover shows a molecular dynamics simulation box consisting of PPV molecules. The box, each side of which is about 7.4 nm, is filled with 60 polymer chains that are 40 monomer units long. The stresses generated upon subjecting the simulation box to small deformatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 0 publications
2
5
0
Order By: Relevance
“…Ramaswamy et al. [ 56 ] showed that the resulting volumetric thermal expansion coefficient, α, from molecular dynamics simulation, defined by Equation , was quite consistent with the experimental observations of Boyer and Spencer [ 57 ] for several common polymers. Using the resulted Tg value, the product α 2 Tg ≅ 0.1, which is consistent with experimental prediction.…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…Ramaswamy et al. [ 56 ] showed that the resulting volumetric thermal expansion coefficient, α, from molecular dynamics simulation, defined by Equation , was quite consistent with the experimental observations of Boyer and Spencer [ 57 ] for several common polymers. Using the resulted Tg value, the product α 2 Tg ≅ 0.1, which is consistent with experimental prediction.…”
Section: Resultssupporting
confidence: 66%
“…[51] Also, as the glass transition of polymers exhibits a free volume dependency relationship, the temperature-free volume relationship was used to examine the glass transition temperatures for all samples. [52] The free volume and occupied volume of PE and ODIN-PEHEMAs boxes were calculated using the Connolly task in the Biovia Materials Studio software. The simulated fractional free volumes (FFV) of the polymers are dependent on the chosen Connolly radius since these were used as the probe particles.…”
Section: Glass Transition Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…However, this technique is nonideal for thin films below 1 µm thick, as the substrate could interfere with the measured modulus . It was shown that the modulus obtained from nanoindentation of 3 µm thick conjugated polymer films have good agreement to values from molecular dynamics simulations . For sub‐100 nm films however, atomic force microscopy (AFM) nanomechanical mapping may be more appropriate.…”
Section: Methods For Characterizing Thin Film Mechanical Propertiesmentioning
confidence: 93%
“…Nanoindentation is another standard technique often used to characterize the tensile modulus of thin films and had been used for conjugated polymers . However, this technique is nonideal for thin films below 1 µm thick, as the substrate could interfere with the measured modulus .…”
Section: Methods For Characterizing Thin Film Mechanical Propertiesmentioning
confidence: 99%